Effects of ginger and ondansetron on intra and postoperative nausea and vomiting in cesarean section under spinal anesthesia: A double-blinded randomized clinical trial - Behzad Imani; Sahar Alizade; Salman Khazaei; Pouran Hajian (Shahrekord University of Medical Sciences, 2023)
Introduction: The occurrence of nausea and vomiting following anesthesia and surgery is a prevalent and distressing issue, ranking second only to pain. In this study, the effects of ginger and ondansetron in mitigating these symptoms in patients who underwent cesarean section surgery were compared. Methods: This double-blinded randomized clinical trial included 150 eligible patients who were randomly assigned to one of three groups: ginger, ondansetron, and control. The ginger group was given one 1000 mg ginger capsule, the ondansetron group was given one 16 mg ondansetron capsule, and the control group was given one placebo capsule. Participants took their designated capsules with 30 mL of water one hour before their scheduled surgery. Nausea intensity and vomiting frequency were assessed throughout the surgical procedure and at post-operation intervals of 0.5, 1, 2, and 4 hours. Results: Compared to the control group, the ginger group had significantly less severe nausea during the surgery (P=0.03) and one hour after surgery (P=0.01). The ginger group also had significantly fewer vomiting episodes during the surgery (P=0.007) and half an hour after surgery (P=0.001). There was no significant difference between the ginger and ondansetron groups regarding the severity of nausea and the number of vomiting (P>0.05). Conclusion: The administration of ginger was found to be successful in alleviating the severity of nausea and vomiting both during and after spinal anesthesia for cesarean section procedures. It could be a viable alternative to ondansetron.